Claiming Incentive Logistics at the Heavy 4th Tuban Cement Project in Indonesia: A Practical Guidance - Subiyanto, Effnu (Technium Social Sciences Journal, 2021)
This practical research aims to be guidance for investors who intend to claiming projects’ incentives offered by Indonesia’s government. Many of them failed to claim such incentives due to lack documents fulfillment since preparation, they mostly unaware, when it needed just realized requiring many revisions and finally came to end-rejection. Scope of this paper is in Indonesia for investors who are in preparation-stage to do project investments. It comes to conclude that remodeling logistics’ execution can successfully reduce to only 7% of logistics costs or far below than Doing Business’ finding. Methodology applied was changing Incoterms to be free on board (FOB) instead of cost and freight (CFR).